Behavioural and physiological indicators to evaluate the transport of steers to the slaughterhouse and its relationship with pH of the beef - Romero Peñuela, Marlyn Hellen (2017)
The aim of the study was to evaluate the transport of steers by behavioral and physiological indicators and its relationship with high pH of the beef at 24 h after slaughter. A total of 56 Zebu steers (2.5 ± 0.2 years old, 429.9 ± 29.3 kg) were evaluated in four trips to the slaughterhouse under similar conditions (route, truck, and driver), where behavioral indicators (affiliative and agonistic interactions, body postures, body direction in the truck and exploration), stress physiological indicators, and beef pH24 were evaluated. No significant differences were observed in the behavioral variables and the muscle pH24 according to the compartments of the truck. The affiliative interactions were more frequent than the agonistic. Hematocrit and cortisol, glucose and creatine kinase blood concentrations showed high values. The 63.5% (n=36) of the carcasses presented pH24 >5.8. These results indicate that the commercial transport with duration of 8 h was a physiological stress factor for Zebu steers, with negative implications on high pH of the beef. The absence of the social mixture favored the cohesion and group stability.